The World Universities’ Response to COVID-19: Remote Online Language Teaching 2021
DOI: 10.14705/rpnet.2021.52.1270
|View full text |Cite
|
Sign up to set email alerts
|

Sudden shift to online learning during the COVID-19 pandemic: the case of Arabic at Qatar University

Abstract: The present chapter focuses on the immediate impact of the COVID-19 pandemic on the higher education sector, presenting the case of the Arabic for Non-Native Speakers Center (ANNS) at Qatar University. It evaluates what actions the center has undertaken to pledge its integrity to the cause of higher education throughout the pandemic and considers a sample of students’ responses to a survey ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Over time, significant advancements have been made in the field of online teaching and learning. Despite the intricacies in transitioning to a fundamentally different teaching approach, our university serves as an exemplary institution that has successfully risen to the challenge of finding solutions to ensure the uninterrupted continuity of education during the pandemic (Heider, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over time, significant advancements have been made in the field of online teaching and learning. Despite the intricacies in transitioning to a fundamentally different teaching approach, our university serves as an exemplary institution that has successfully risen to the challenge of finding solutions to ensure the uninterrupted continuity of education during the pandemic (Heider, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In later stages, Hussain et al (2020) [23] observed Qatar University's swift transition to high-quality distance learning, facilitated by the institution's long-standing and widespread use of foundational technological resources, underscoring the importance of institutional readiness in higher education. On the other hand, Heider (2021) [24] acknowledge effective implementations for remote education at Qatar University's Arabic for Non-Native Center. Nonetheless, challenges persist in verifying student identities during live streaming classes, exacerbated by insufficient connectivity quality for streaming access, among other factors.…”
Section: Introductionmentioning
confidence: 99%